Serological evidence of Brucella infections in dairy cattle in Haryana, India - Lindahl, Johanna F.; Kumar, N.G.; Deka, Ram Pratim; Shome, R.; Grace, Delia (Informa UK Limited, 2018)
Background: In India, milk production is important for both the economy and the provision of nutritious food. However, the productivity of the livestock is affected by circulating infectious diseases, and some zoonotic diseases, such as brucellosis, may cause a heavy impact on the farm as the disease cause abortions and reproductive failures in bovines, with chronic febrile illness in humans. Methods: 249 dairy farms in the state of Haryana, India, were interviewed, and collected raw milk from 81 were analyzed for antibodies towards Brucella abortus. Results: More samples were positive using milk ring test (MRT) (55.6%, 45/81) than using enzyme-linked immunosorbent assay (ELISA) (29.6%, 24/81), with all ELISA positive samples also positive in MRT. The ELISA results were used for risk factor analyses. Seropositive farms were significantly (p = 0.015) larger than seronegative, with an average 7.9 cattle, compared to 4.9. Seropositive farms were more likely to report stillbirth occurring the last year, and a significantly higher proportion of seropositive farms reported retained placenta (odds ratio 5.2). Conclusion: This study showed that Brucella seroprevalence is high among farms in Haryana, and a control program is needed to ensure improved human and animal health, as well as improved livestock productivity.